ANSYS investigation of solar photovoltaic temperature distribution for improved efficiency - Paul Rousseau; Hassan Nouri (International Journal of Advances in Applied Sciences, 2023)
A computational analysis of the influence of varying solar module material properties on operating temperature is presented and related to electrical conversion efficiency through the devised method. By varying the properties of density, specific heat capacity, and isotropic thermal conductivity for each material that comprises a solar module, density, and specific heat capacity were found to have the greatest influence on decreasing the operating temperature when increased by a factor of 50% for the glass layer, resulting in a decrease in temperature of 5.33 °C. Utilizing the devised method, which is based on the work of Palumbo, this temperature decrease was correlated to an electrical efficiency increase of 3.08%.